1997
DOI: 10.1113/jphysiol.1997.sp021936
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐1 potently stimulates chloride secretion and inhibits Na(+)‐glucose absorption in human intestine in vitro.

Abstract: 1. Serosally added synthetic endothelin-1 (ET-1) increased short-circuit current (I,,) across isolated muscle-stripped human colonic mucosa in vitro. Bumetanide inhibited I., responses,indicating that ET-1 stimulates electrogenic Cl-secretion. 2. In isolated human jejunal mucosa, ET-1 exhibited a concentration-dependent dual action. At low concentrations it induced rapid increases in ISC and these were inhibited by bumetanide. 4. Electron microprobe analyses of cryosections of human jejunum showed that ET-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…ET-1 induced glucose uptake in 3T3-L1 adipocytes and rat cardiomyocytes [41Á43]. In addition, ET-1 inhibited sodium-coupled glucose absorption in the small intestine of rat in vitro [25]. In our experiments, the fasting-induced ET-1 expression was decreased at 2 h after re-feeding, when blood glucose concentration might have increased from a low to a normal level.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…ET-1 induced glucose uptake in 3T3-L1 adipocytes and rat cardiomyocytes [41Á43]. In addition, ET-1 inhibited sodium-coupled glucose absorption in the small intestine of rat in vitro [25]. In our experiments, the fasting-induced ET-1 expression was decreased at 2 h after re-feeding, when blood glucose concentration might have increased from a low to a normal level.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, it has been reported that loss of ET-3 and/or ETB receptor function may be involved in the abnormal development of neural crest-derived cells, causing Hirschsprung's disease [19Á21]. It has also been observed that ET-1 and ET-3 increase chloride secretion in rat [22,23] and rabbit [24] colon in vitro and that ET-1 inhibits glucose-coupled sodium absorption [25] and enhances bicarbonate secretion in the small intestine of rat [26] in vitro. However, the effect of ET-1 in mouse colon is not known.…”
Section: Introductionmentioning
confidence: 94%
“…However, the effects of ET-1 on epithelial Cl secretion-i.e., the nature of the effect (stimulation versus inhibition), its magnitude and its mechanismdiffer between tissues and between species. In human gallbladder, ET-1 inhibits cAMP-induced Cl secretion (16), whereas in human intestine, ET-1 stimulates Cl secretion in part via the activation of enteric nerves (17). In dog airways, ET-1 increases electrogenic Cl secretion (3,18,19), and this effect is mediated via the secondary production of cyclooxygenase products such as PGE 2 .…”
mentioning
confidence: 99%
“…The paper by Kuhn et al (1997) The intestine is a difficult tissue in which to explore the cellular basis for physiological responses. It was among the first tissues studied in the classic Ussing chamber, which electrically measures active charge movement across epithelia.…”
mentioning
confidence: 99%
“…This diversity has contributed to confusion about mechanisms of endothelin action. In the work of Kuhn et al (1997) the Ussing chamber is supplemented with isotopic fluxes and electron microprobe analysis so that a multifaceted approach is used to address differences in small versus large intestine, neural versus epithelial targets, and actions along the crypt-to-villus axis, all using human tissue. By playing to the strengths of the different methods, we are provided with a vision of endothelin action in which a direct regulatory effect on the Nae-glucose cotransporter itself (SGLT1) is implicated, and in which neuronal pathways (i.e.…”
mentioning
confidence: 99%